Production of food bodies on the reproductive organs of myrmecophytic Macaranga species (Euphorbiaceae): effects on interactions with herbivores and pollinators. Issue 3 (6th May 2013) - Yamasaki, Eri; Inui, Yoko; Sakai, Shoko
Abstract: In protective ant–plant mutualisms, plants offer ants food (such as extrafloral nectar and/or food bodies) and ants protect plants from herbivores. However, ants often negatively affect plant reproduction by deterring pollinators. The aggressive protection that mutualistic ants provide to some myrmecophytes may enhance this negative effect in comparison to plant species that are facultatively protected by ants. Because little is known about the processes by which myrmecophytes are pollinated in the presence of ant guards, we examined ant interactions with herbivores and pollinators on plant reproductive organs. We examined eight myrmecophytic and three nonmyrmecophytic Macaranga species in Borneo. Most of the species studied are pollinated by thrips breeding in the inflorescences. Seven of eight myrmecophytic species produced food bodies on young inflorescences and/or immature fruits. Food body production was associated with increased ant abundance on inflorescences of the three species observed. The exclusion of ants from inflorescences of one species without food rewards resulted in increased herbivory damage. In contrast, ant exclusion had no effect on the number of pollinator thrips. The absence of thrips pollinator deterrence by ants may be due to the presence of protective bracteoles that limit ants, but not pollinators, from accessing flowers. This unique mechanism may account for simultaneous thrips pollination and ant defense of inflorescences.